2014
DOI: 10.1111/jasp.12290
|View full text |Cite
|
Sign up to set email alerts
|

By name or by deed? Identifying the source of the feminist stigma

Abstract: Prejudice and discrimination against feminists were explored across two contexts, a workplace and a social setting. We examined university students' reactions to a woman who called herself a feminist, behaved like a feminist by challenging sexism, did both, or did neither. In Study 1, participants (N = 177) evaluated a job candidate less favorably when she called herself a feminist after controlling for perceived assertiveness and participants' feminist self‐identification. However, our results showed no evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Our samples are limited to Spanish college students. In recent years, gender issues have become an important political agenda topic in Spain (Grodira et al, 2018), so despite the feminist stigma (Anderson, 2009;Anastosopoulos and Desmarais, 2015), feminist identification is rising in Spain (Álvarez, 2018;Centro de Investigaciones Sociológicas [Sociological Research Center], 2018). Thus, it would be important to replicate these results in other countries, as well as to study these processes with the general population to see if they can be generalized.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Our samples are limited to Spanish college students. In recent years, gender issues have become an important political agenda topic in Spain (Grodira et al, 2018), so despite the feminist stigma (Anderson, 2009;Anastosopoulos and Desmarais, 2015), feminist identification is rising in Spain (Álvarez, 2018;Centro de Investigaciones Sociológicas [Sociological Research Center], 2018). Thus, it would be important to replicate these results in other countries, as well as to study these processes with the general population to see if they can be generalized.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Twenge and Zucker (1999) suggested that the misperception of others' attitudes towards feminism may have led to women rejecting a feminist identity; even though studies have revealed that women's stereotypes of feminists are generally positive, they assume others evaluate feminists negatively (Ramsey et al, 2007;Roy et al, 2007). In particular, it has been found that some women believed that men do not like feminists (Alexander & Ryan, 1997;Anastasopoulos and Desmarais, 2015). Interestingly, Ramsey et al (2007) acknowledged this trend for women believing others hold negative stereotypes, but predicted that self-identified feminists would be more likely than nonfeminists to assume that others consider feminists in a positive light.…”
mentioning
confidence: 99%
“…working on behalf of women is often reinterpreted as working against men (Anastasopoulos & Desmarais, 2015). In several studies, participants have described feminists as "man-hating lesbians" or women in search of reverse discrimination (Ogletree, Diaz, & Padilla, 2017;Ramsey et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Anastasopoulos & Desmarais (), the surname of the first author was spelled incorrectly as Anastosopoulos. The author's correct surname should be Anastasopoulos.…”
mentioning
confidence: 99%